Assessment of the Burnout Level in Health Care Worker During COVD 19 - Mustafa Kareem Jawad; Dhiaa Abd Al-Rasoul Abd Al-Reda; Waleed Ali Armeah; Asmaa Jabbar Abdulhussein (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Health care workers are considered the first and real repelling line in the face of the COVID19pandemic, and therefore they have an increased workload, and stress. Understanding risk for burnout iscritical to supporting health workers and maintaining the quality of healthcare during the pandemic.Methods: A cross-sectional study design could be used to assessment the level of burnout during COVID19. Included 1000 samples as a healthcare worker involved in the study by used of convenience samplingtechnic , The study has been carried out in Iraqi, conducted throughout the period of April 15th, to July 19th,2020. A self-administered questionnaire and Maslach Burnout Inventory Human Service Survey were usedto collect data.Results: Overall, burnout were high level among 59.9 % of the participants in the study. High workloadand intention to leave were associated with burnout at statistically significant (P<0.05), and high significantrelationship between demographic characteristics (age, gender, level of education, job title, work place ) andlevel of burnout (P<0.05).Conclusions: The high level of burnout identified among health workers is mainly related to the highworkload and psychological stress fronting them during COVID 19, as well as the lack of personal equipmentnecessary to protect themselves from this epidemic.